FRI0449 Presence of Abnormal Capillary Dilations in Primary Raynaud Phenomenon Subjects Might Anticipate the Transition to the Capillaroscopic "Early" Scleroderma Pattern: A Case Control Study. (9th June 2015) - Trombetta, A.C.; Sulli, A.; Pizzorni, C.; Meroni, M.; Cariti, C.; Paolino, S.; Ruaro, B.; Cutolo, M.
Abstract : Background: Nailfold Video Capillaroscopy (NVC) is a reliable and safe method to qualitatively differentiate Primary (PRP) from Secondary Raynaud Phenomenon (SRP) allowing early diagnosis of systemic sclerosis (SSc) SRP-associated ("early" scleroderma pattern) 1, 2 . Quantitative evaluation by NVC was demonstrated to be of great value for the analysis of abnormal capillary parameters 2 . Objectives: To investigate the presence of diameter abnormalities, i.e. dilations >20μm, and their localization at level of capillaries, during the NVC follow up of PRP subjects, before their transition to SRP. Methods: We performed a case-control study, over a total population of 191 PRP subjects (mean RP duration: 7.70 years), with a NVC follow-up of 42.77±35.80 months (3.56±2.98 years). PRP subjects were then classified as SSc SRP-associated, based on the appearance of the "early" scleroderma pattern and/or ANA positivity. Concomitant therapies and comorbidities were evaluated to avoid confounding factors 3 . A single operator performed the NVC and results were separately checked by three experts (PC, SA, CM), in blind. Practically, the observer (TAC), using a dedicated software (Videocap, DS MediGroup, Milan, Italy), measured on NVC images the major dilation of capillary loop's branches (arterial, venous, apical). The mean diameter value for each enlarged branch (arterial, venous, apical) and therefore the total mean diameter value of all observed dilations, were calculated in each PRP subject. Mean diameter values were then correlated with all the considered clinical variables. Mann Whitney U and χ 2 tests were used to calculate the differencies in the observed values between the two populations. Results: A significant presence of abnormal dilations for both arterial and venous branches, was found in PRP subjects before their transition to SRP, compared to stable PRP subjects (p<0.0001), with a mean time of 29.19±26.94 months for transition. No significant differences were observed for apical dilations (p=0.07) (table ). No significant correlations between the rate of dilations and clinical characteristics were detected. Conclusions: The study shows that abnormal dilations of capillary diameter at the level of arterial and/or venous branches, are detectable by NVC, and are significantly expressed in PRP subjects that will develop a SRP associated to SSc. Therefore, the progressive presence of abnormal capillary dilations in PRP subjects, over at least 3.56 years of follow up, should be considered as a possible very early NVC signal of transition to the "early" scleroderma pattern. References: Cutolo M et al. 2000;27:155–60. Cutolo M et al. Best Pract Res Clin Rheumatol. 2013;27(2):237-48. Smith V at al. J Rheumatol. 2013;40:2023-8. Disclosure of Interest: None declared